TMbarrier: speculative barriers using hardware transactional memory - Pedrero-Luque, Manuel; Gutiérrez-Carrasco, Eladio Damián; Plata-González, Óscar Guillermo (My University, 2018)
Barrier is a very common synchronization method used in parallel programming. Barriers are used typically to enforce a partial thread execution order, since there may be dependences between code sections before and after the barrier. This work proposes TMbarrier, a new design of a barrier intended to be used in transactional applications. TMbarrier allows threads to continue executing speculatively after the barrier assuming that there are not dependences with safe threads that have not yet reached the barrier. Our design leverages transactional memory (TM) (specifically, the implementation offered by the IBM POWER8 processor) to hold the speculative updates and to detect possible conflicts between speculative and safe threads. Despite the limitations of the best-effort hardware TM implementation present in current processors, experiments show a reduction in wasted time due to synchronization compared to standard barriers.
Keywords: Hardware; Speculation; Hardware transactional memory; IBM power8; Parallel computing